2012
DOI: 10.1002/mnfr.201100719
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chromium dinicocysteinate supplementation on circulating levels of insulin, TNF‐α, oxidative stress, and insulin resistance in type 2 diabetic subjects: Randomized, double‐blind, placebo‐controlled study

Abstract: Background and Aims Chromium and cysteine supplementation have been shown to improve glucose metabolism in animal studies. This study examined the hypothesis that chromium dinicocysteinate (CDNC), a complex of chromium and L-cysteine, is beneficial in lowering oxidative stress, vascular inflammation and glycemia in type 2 diabetic patients. Methods Type 2 diabetic patients enrolled in this study were given placebo for one month for stabilization and then randomized into one of three groups: placebo (P), chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 41 publications
(46 reference statements)
0
52
0
3
Order By: Relevance
“…All were in English. Of these, 22 studies assessed chromium as a single supplement . Two others evaluated chromium plus biotin .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All were in English. Of these, 22 studies assessed chromium as a single supplement . Two others evaluated chromium plus biotin .…”
Section: Resultsmentioning
confidence: 99%
“…Based on its mechanisms of action, chromium administered as a supplement to antidiabetic agents may help improve glucose variables in diabetes. Nonetheless, the reported effects of chromium mono‐ and combined supplementation on glucose and lipid profiles in diabetes have been inconsistent . Three meta‐analyses have been previously published .…”
Section: What Is Known and Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…Along with affecting insulin-mediated pathways, chromium [52][53][54], and zinc [55][56][57] also decrease inflammation that is known to play a significant role in obesity and insulin resistance development [58]. Therefore, a significant interplay between trace elements and insulin resistance exist.…”
Section: Trace Elements In Insulin Signalingmentioning
confidence: 97%
“…So they concluded that it can be a potent adjunct therapy in type 2 diabetics 39 . In our study, Chromium dinicocysteinate did not demonstrated significant effect on HbA1C but showed significant effect on biomarkers of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%